FAKTOR-FAKTOR YANG MEMENGARUHI KEPATUHAN DIET PASIEN GAGAL GINJAL KRONIK YANG MENDAPAT TERAPI HEMODIALISA DI RUANG HEMODIALISA RSUD Dr. PIRNGADI KOTA MEDAN TAHUN 2015 - Amira Permata Sari Tarigan; Endang Susilawati; Chandra F Zendrato (Poltekkes Kemenkes Medan, 2016)
Chronic kidney failure patients treated by hemodialysis therapy should be consistent in participating in dieting program in order to forestall the incidence of nutrition deficiency, liquid and electrolyte imbalance, and the incidence of the excessive accumulation of metabolism residual. Compliance in dieting program is one of the factors which contribute to the success or failure in hemodialysis therapy. The objective of the research was to find out some factors which influenced compliance in dieting of chronic kidney failure patients who got hemodialysis therapy in Hemodialysis Room of RSUD dr. Pirngadi, Medan. The research used descriptive method with cross sectional design. The samples were 35 respondents, taken by using purposive sampling technique. The instruments of the research were questionnaires and food recall. The result of the research showed that 19 respondents (54.3%) did not quite understand the instruction, 26 respondents (74.3%) had good interaction, 21 respondents (60%) lack of support, 31 respondents (88.6%) did not comply with dieting program, and 4 respondents (11.4%) complied with dieting program. The factor which influenced the compliance of the majority of patients was interaction quality. Patients had good understanding in instruction, good interaction quality, and family support. Only a small number of patients complied with dieting. Patients’ awareness of diet is very important. The majority of patients did not comply with dieting program.